Late developing supernumerary teeth and congenital absence of the upper right lateral incisor in the maxillary anterior region: a rare case report - Yanyan Xie; Hong Gao; Lin Xing; Mingna Tang (BMC Oral Health)
Abstract Background Numerous non-syndromic late developing supernumerary teeth have been published in the premolar regions, but similar findings in the maxillary anterior regions as in this case are rarely found; even rarer is hypodontia occurring in the same region; this simultaneous occurrence is known as hypohyperdontia. Case presentation This paper reports a case of two mesiodens and a late developing supernumerary tooth appearing successively in the maxillary anterior region, resulting in severe rotation and displacement of adjacent incisors. By regular clinical and radiological monitoring, we have implemented appropriate treatment promptly and obtained good therapeutic effects. Conclusions Radiographic examination of the jaws is crucial for early diagnosing hypodontia and hyperdontia. The treatment for hypohyperdontia varies depending on individual circumstances and requires an interdisciplinary strategy. To patients with a history of supernumerary teeth and severe misalignment of adjacent normal teeth, clinical and appropriate radiographic monitoring are essential for early diagnosis of late developing supernumerary teeth and assessment of root resorption. Only by detecting these abnormalities early can we implement the most appropriate treatment promptly, minimize future complications, and simplify treatment procedures.